2008
DOI: 10.1111/j.1742-7843.2008.00260.x
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone Ameliorates Renal Oxidative Damage and Proliferative Response Induced by Mercuric Chloride in Rats

Abstract: Abstract:We tested the hypothesis if thymoquinone (2-isopropyl-5-methyl-1,4-benzoquinone) could ameliorate renal oxidative damage and proliferative response induced by mercuric chloride (HgCl 2 ) in rats. HgCl 2 (3 mg/kg) was administered subcutaneously to each one of two groups of rats: (i) HgCl 2 -thymoquinone group that received thymoquinone (10 mg/kg/ day); and (ii) HgCl 2 group that received vehicle instead of thymoquinone. A third group of rats was reserved as control group. Rats were killed 24, 48 and 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 43 publications
(66 reference statements)
6
41
1
2
Order By: Relevance
“…In different toxicity studies it was found that the administration of TQ led to decreased MDA levels [30,33,34,35]. In the present study, TQ protected prostate tissue from NO- and MDA-dependent oxidative stress when administered at 24, 48, and 72 h (p < 0.05; fig.…”
Section: Discussionsupporting
confidence: 56%
“…In different toxicity studies it was found that the administration of TQ led to decreased MDA levels [30,33,34,35]. In the present study, TQ protected prostate tissue from NO- and MDA-dependent oxidative stress when administered at 24, 48, and 72 h (p < 0.05; fig.…”
Section: Discussionsupporting
confidence: 56%
“…Fouda et al [70] investigated protective effects of TQ in mercuric chloride (HgCl 2 )-induced nephrotoxicity. Their results showed that the deterioration of antioxidant enzymes, increase in serum Cr and histological injury induced by HgCl 2 were markedly ameliorated by TQ therapy (10 mg/kg/day).…”
Section: Resultsmentioning
confidence: 99%
“…TQ (2-isopropyl-5-methyl-1,4-benzoquinone), the main active component of the essential oil of Nigella sativa seeds, has various pharmacological effects. It has been reported to display various pharmacological activities such as antioxidant (7), antidiabetic (8), cardioprotective (9), hepatoprotective (10), neuroprotective (11), nephroprotective (12), anti-infl ammatory (13), anti-mutagenic (14), and anticancer (15) effects. TQ is of low toxicity (LD50 2.4 g/kg) and is well tolerated when given subchronically till 90 mg/ kg/day for 90 days (16).…”
Section: Introductionmentioning
confidence: 99%